Answer: 9
Step-by-step explanation:
2X+5=3X-4
-2X. -2X
5= X-4
+4
9=X
Hi there!
First we need to remember the following.
![(f + g)(x) = f(x) + g(x)](https://tex.z-dn.net/?f=%28f%20%2B%20g%29%28x%29%20%3D%20f%28x%29%20%2B%20g%28x%29)
Now substitute both of the formulas.
![(f + g)(x) = ({3}^{x} + 10x)+ (4x - 2)](https://tex.z-dn.net/?f=%28f%20%2B%20g%29%28x%29%20%3D%20%28%7B3%7D%5E%7Bx%7D%20%2B%2010x%29%2B%20%284x%20-%202%29)
Work out the parenthesis.
![(f + g)(x) = {3}^{x} + 10x + 4x - 2](https://tex.z-dn.net/?f=%28f%20%2B%20g%29%28x%29%20%3D%20%7B3%7D%5E%7Bx%7D%20%2B%2010x%20%2B%204x%20-%202)
And finally collect terms.
![(f + g)(x) = {3}^{x} + 14x - 2](https://tex.z-dn.net/?f=%28f%20%2B%20g%29%28x%29%20%3D%20%7B3%7D%5E%7Bx%7D%20%2B%2014x%20-%202)
~ Hope this helps you!
7 and 10 is half
so we expect the people come to wedding half of 120÷2=60 people
i just try
Hey user☺☺
The graph will have no solution.
Hope it works